Que literatura no Ensino Médio? : dos documentos oficiais aos livros didáticos - Costa, Karl Roney Torres (2015)
This research proposes the analysis of conceptions of literary phenomenon and the teaching of literature present in three official documents of basic education, namely: os Parâmetros Curriculares Nacionais – Ensino Médio (PCNEM); os Parâmetros Curriculares Nacionais + Ensino Médio (PCN+); e as Orientações Curriculares para o Ensino Médio (OCEM), as well as the impact of these documents on approach of literature by textbooks. We assume that each concept of literature builds pedagogical practices and quirky content, i. e, methodology and distinct object. From this premise, this paper will discuss the pedagogical implications precisely the notion of literature presented by each of these documents and, then, it will ascertain the repercussion of these ideas and prescriptions on some textbooks suggested by Programa Nacional do Livro Didático (PNLD). In order to support this study; will draw in particular the ideas of theorists who in recent decades have undertaken a critical review of literary theories, like Terry Eagleton, Antoine Compagnon, Tzvetan Todorov. We will also use as a theoretical written by national authors who treat the teaching of literature, namely: William Roberto Cereja, Marisa Lajolo, Ivanda Martins among others.